Laterally-continuous dolomite layers of the Miocene Pisco Formation (East Pisco Basin, Peru): A window into past cyclical changes of the diagenetic environment. (January 2023) - Malinverno, Elisa; Bosio, Giulia; Gioncada, Anna; Cimò, Raffaella; Andò, Sergio; Mariani, Luca; Coletti, Giovanni; Boschi, Chiara; Gariboldi, Karen; Galimberti, Lucia; Bianucci, Giovanni; Urbina, Mario; et al.
Abstract: Along the Peruvian coast, the sedimentary succession of the East Pisco Basin is exposed in the Ica Desert. At Cerro Los Quesos, laterally continuous dolomite layers characterise the diatomaceous sediments of the P2 sequence of the Miocene Pisco Formation, where a large number of marine vertebrates are exceptionally preserved, many enclosed in dolomite nodules. In this work, cemented layers from this sequence were described and sampled for petrographic, chemical, microscopic and isotopic analyses. Dolomite occurs in continuous 10–50 cm thick well cemented layers, formed by sediment of different nature: biogenic, terrigenous, volcanoclastic, and phosphatic. The underlying sediments exhibit a yellow layer with sparse dolomite crystals, a black layer with abundant Mn-oxides, and a reddish layer rich in Fe-oxides, indicating redox-related fronts. Two generations of dolomite can be recognised: an early diagenetic microcrystalline one, and a sparry one, filling the large cavities. As observed in both thin sections and on broken surfaces, microcrystalline dolomite also fills the inner spaces of the diatom areolae replicating their finest ultrastructure, such as foramina and cribra and replace calcite shells of foraminifera. δ 18 O and δ 13 C values from the microcrystalline dolomite of two layers, selected based on the absence of other carbonate phases (e.g. calcite) and the lack of sparry cement, are in agreement with those reported for the Peru margin and fall in the fields of either sulphate-reduction or methanogenesis. All the data point to dolomite precipitation associated with low-temperature early diagenesis that typically occurs in upwelling settings, where high surface water productivity is responsible for high rates of organic carbon flux to the sea bottom and for the cyclical oxygen depletion at the bottom. Such conditions also promote high abundances of marine vertebrates and the exceptional preservation of their skeletons in the sediments. Highlights: Carbonate layers from the Miocene Pisco Formation are cemented by low Fe microcrystalline dolomite with clotted texture. Dolomite layers preserve undeformed diatoms, suggesting early dolomite precipitation before significant compaction. Early dolomite precipitation is supported by its relatively high molar % Ca content, intermediate degree of crystal ordering. Stable isotopes are consistent with early diagenetic dolomite precipitation, Frequent dolomite layers coincide with abundant marine vertebrate fossils and point to cyclical bottom oxygen variations.